2008
DOI: 10.1002/arch.20256
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin B1 detoxification by CYP321A1 in Helicoverpa zea

Abstract: The polyphagous corn earworm Helicoverpa zea frequently encounters aflatoxins, mycotoxins produced by the pathogens Aspergillus flavus and A. parasiticus, which infect many of this herbivore's host plants. While aflatoxin B1 metabolism by midgut enzymes isolated from fifth instars feeding on control diets was not detected, this compound was metabolized by midgut enzymes isolated from larvae consuming diets supplemented with xanthotoxin, coumarin, or indole-3-carbinol, phytochemicals that are likely to co-occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 44 publications
1
54
0
1
Order By: Relevance
“…Another instance occurs in Helicoverpa zea, the cotton bollworm; CYP6B8 is induced by xanthotoxin and the enzyme metabolizes the toxin (Li et al, 2003). In addition, several reports have suggested that some of insect P450s of the CYP4, CYP9, CYP28, and CYP6 families are induced by host plants, or participate in the detoxifi cation of the host-plant allelochemicals (Danielson et al, 1997David et al, 2006;Fogleman et al, 1998;Niu et al, 2008;Snyder et al, 1995;Stevens et al, 2000;Yang et al, 2007;Zhou et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Another instance occurs in Helicoverpa zea, the cotton bollworm; CYP6B8 is induced by xanthotoxin and the enzyme metabolizes the toxin (Li et al, 2003). In addition, several reports have suggested that some of insect P450s of the CYP4, CYP9, CYP28, and CYP6 families are induced by host plants, or participate in the detoxifi cation of the host-plant allelochemicals (Danielson et al, 1997David et al, 2006;Fogleman et al, 1998;Niu et al, 2008;Snyder et al, 1995;Stevens et al, 2000;Yang et al, 2007;Zhou et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of P450s in the bioactivation of aflatoxin in H. zea is supported by the significant decrease in the toxicity of AFB1 when the P450 inhibitor piperonyl butoxide (PBO) is included in the assay (Zeng et al 2006), a result that is consistent with bioactivation of aflatoxin to more toxic derivatives by one or more P450s expressed in fourth and fifth instars. Molecular modeling data predict that aflatoxin can fit in the catalytic sites of CYP6B8 (Niu et al 2008), which may be responsible for the bioactivation of aflatoxin in response to MeJA and SA.…”
Section: Resultsmentioning
confidence: 98%
“…To date, no epoxide metabolite of aflatoxin has been identified in H. zea, although CYP321A1 expressed heterologously converts aflatoxin to aflatoxin P1, its Odemethylated product (Niu et al 2008). The involvement of P450s in the bioactivation of aflatoxin in H. zea is supported by the significant decrease in the toxicity of AFB1 when the P450 inhibitor piperonyl butoxide (PBO) is included in the assay (Zeng et al 2006), a result that is consistent with bioactivation of aflatoxin to more toxic derivatives by one or more P450s expressed in fourth and fifth instars.…”
Section: Resultsmentioning
confidence: 99%
“…Altered gene expression patterns in detoxiWcation pathways have been documented in response to a host shift in cactus-breeding Drosophila (Matzkin et al 2006), and detoxiWcation processes in Drosophila have been suggested to be an adaptation to a feeding habitat spoilt with various toxic microbial products (Berenbaum 2002). Prominent Aspergillus mycotoxins have been shown to have mutagenic eVects on Spodoptera littoralis larvae, impairing spermatogenesis and hence causing infertility in adult moths (Abdou et al 1984); yet mechanisms appear to exist that enable insects to reduce toxicity of mycotoxins (Foerster and Würgler 1984;Lee and Campbell 2000;Niu et al 2008). Thus, one hypothesis is that the evolved resistance against A. nidulans in Drosophila reXects an enhanced protection of germlines against fungal compounds, which might improve (or even enable in the Wrst place) reproductive output in both sexes.…”
Section: Discussionmentioning
confidence: 99%